Incidente de impacto fiscal (2017)
The article is to determine the events in which the Fiscal Impact Incident could be filed based on the obligation to guarantee the principle of fiscal sustainability and not to limit its competence to the Ministries and / or Attorney General of the Nation. To this end, the structure of the Fiscal Impact Incident will be analyzed, the cases or events in which the fiscal impact incident is reported, the relationship between the Fiscal Impact Incident and the principle of fiscal sustainability, the criteria of competence to interpose the Fiscal Impact Incident. Incident of Fiscal Impact. The foregoing, in order to determine whether the nature of the Fiscal Impact Incident has changed with respect to the discretionary activity of the competent administrative authorities to intervene, affecting the principles governing administrative procedures and the Constitutional mandate.